Antibiotic prophylaxis may be still required among transperineal prostate biopsies of diabetics: a cohort study - Ma, Feiyue; Zhang, Yu (Frontiers in Medicine, 2025)
BackgroundTransperineal prostate biopsy (TP-PB) is considered the gold standard for suspected prostate cancer patients. However, the rate of transperineal prostate biopsy-related urinary tract infections (UTIs) has been calculated to be as high as 3%. This study aimed to discuss the incidence of transperineal prostate biopsy -related infections among diabetic patients who underwent antibiotic prophylaxis (AP) or not.MethodsThe monocentric, comparative, observational cohort study was carried out at Xiangshan County First People’s Hospital Medical Health Group, China between January 2021 and January 2023. The study included 246 diabetic men suspected of having prostate cancer who underwent transperineal prostate biopsy. One group was transperineal prostate biopsy with no antibiotic prophylaxis (Group A-no AP, n = 120, 48.8%), and the other was given a 3 days of oral antibiotics (Group B-AP, n = 126, 51.2%). Data on primary symptoms, urine culture (UC), urinary tract infections incidence, and prostate biopsy -related sequela were gathered 2 weeks following the prostate biopsy.ResultsA total of 246 patients were involved, including 120 in Group A (67.4 ± 7.2 years) and 126 in Group B (68.5 ± 7.0 years) (p = 0.215). Prostate-specific antigen (PSA) levels were 16.1 ± 23.8 vs. 15.9 ± 22.3 ng/ml (p = 0.942), and the prostate cancer detection rate was 58% vs. 57.5% (p = 0.847). The incidence of asymptomatic bacteriuria was significantly higher (8/120, 6.7%) in Group A vs. Group B (1/126, 0.8%) (RR 8.4, 95% CI: 1.1–72.5, p < 0.001). Similarly, urinary irritation symptoms occurred in 30/120 (25.0%) vs. 5/126 (4.0%) patients (RR 6.3, 95% CI: 3.0–21.6, p < 0.001), fever in 9/120 (7.5%) vs. 1/126 (0.8%) (RR 9.5, 95% CI: 1.3–81.3, p = 0.001), and UTIs in 5/120 (4.2%) vs. 1/126 (0.8%) (RR 5.3, 95% CI: 0.63–47.2, p = 0.001), respectively. Notably, sepsis was not detected in either group.ConclusionAntibiotic prophylaxis could decrease the incidence of transperineal prostate biopsy-related infections among diabetic patients.